118k views
25 votes
3.) Solve:
5x + 3- 3x = 2(x + 3) - 5

2 Answers

10 votes

Answer:

0 = -2

Explanation:

User Brandog
by
5.5k points
12 votes

Answer:

no answer.

Explanation:

5x + 3 - 3x = 2(x + 3) - 5 Simplify the left.

2x + 3 = 2(x + 3) - 5 Remove the brackets

2x + 3 = 2x + 6 - 5 Simply the right

2x + 3 = 2x + 1

It doesn't matter what you do, this is going to give you an impossible answer. The 2x's will cancel out and you will get 3 = 1 which is impossible.

User Fabio Nolasco
by
6.5k points